2012 6th Advanced Satellite Multimedia Systems Conference (ASMS) and 12th Signal Processing for Space Communications Workshop ( 2012
DOI: 10.1109/asms-spsc.2012.6333095
|View full text |Cite
|
Sign up to set email alerts
|

Communications over phase-noise channels: A tutorial review

Abstract: In this tutorial paper, we first review the main information-theoretic results on channels affected by a timevarying phase noise. The main maximum a posteriori symbol detection algorithms to be employed in such a challenging scenario are then described considering linear modulations and advanced coding schemes based on iterative detection and decoding. The role of pilot symbols will be also discussed. , as well as for powerful channel codes to be decoded iteratively, such as turbo codes or lowdensity parity-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Prominent examples of channels with memory are the intersymbol interference channel, the phase noise channel, and the fading channel. Among channels with memory, the phase noise channel is considered here, a recent tutorial on the subject being [1].…”
Section: Introductionmentioning
confidence: 99%
“…Prominent examples of channels with memory are the intersymbol interference channel, the phase noise channel, and the fading channel. Among channels with memory, the phase noise channel is considered here, a recent tutorial on the subject being [1].…”
Section: Introductionmentioning
confidence: 99%
“…We elaborate further on the accuracy of the model (1) in Section II-B. We assume that the phase-noise samples {θ k } form a Wiener process [7], i.e.,…”
Section: A the Input-output Relationmentioning
confidence: 99%
“…Unfortunately, the capacity of the phase-noise channel is not known in closed form even for simple channel models, although capacity bounds and asymptotic results in the limiting regime of high SNR have been reported in the literature. Lapidoth characterized the capacity of the general class of stationary phase-noise channels (the widely used Wiener model [7] belongs to this class) in the high-SNR regime [8]. Specifically, he showed that whenever the phase-noise process has finite differential-entropy rate, the high-SNR capacity is equal to half the capacity of an AWGN channel with the same SNR, plus a correction term that accounts for the memory in the phase-noise process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase noise is due to both laser oscillators used for up-and down-conversion [4], and to crossphase modulation that arises in wavelength-division-multiplexing systems [5]. 5 A recent tutorial on transmission over phase noise channels is [6].…”
Section: Introductionmentioning
confidence: 99%